Large-Scale Measurements of Thermospheric Dynamics with a Multisite Fabry-Perot Interferometer Network: Overview of Plans and Results from Midlatitude Measurements - Jonathan J. Makela; John W. Meriwether; Aaron J. Ridley; Marco Ciocca; Michael W. Castellez (International Journal of Geophysics)
The North American Thermosphere Ionosphere Observing Network (NATION), comprising a new network of Fabry-Perot interferometers (FPIs), to be deployed in the Midwest of the United States of America is described. FPIs will initially be deployed to four sites to make coordinated measurements of the neutral winds and temperature in the Earth's thermosphere using measurements of the 630 nm redline emission. The observing strategy of the network will take into account local observing conditions, and common volume measurements from multiple sites will be made in order to estimate local vector wind quantities. The network described is expandable, and as additional FPI sites are installed in North America, or elsewhere, the goal of providing the upper atmospheric research community with a robust dataset of neutral winds and temperatures can be achieved.